1991
DOI: 10.1203/00006450-199105010-00016
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Mice Have Low Susceptibility to Paracetamol Toxicity

Abstract: ABSTRACT. The hepatotoxicity of paracetamol in mice of 2, 3, 8-10, 24-26, 32-34, and 52-54 wk of age was determined by lethality data, histopathologic examination of the liver, and appearance of glutamate-pyruvate transaminase and glutamate-oxaloacetate transaminase activities in the plasma over an 8-h exposure period. At a dose of 300 mg/kg, there was evidence of hepatocytic necrosis and transaminase leakage in the 32-to 34-and 52-to 54-wk-old mice, but lethality was only recorded in the oldest age group. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…The results of ALT and AST levels in plasma as well as H&E staining confirmed an injury of liver in adult mice as expected. Mice at younger ages were reported to be more resistant to AILI (Adamson et al, 1991). In the present study, the resistance to AILI in the mice at the infant age was further confirmed.…”
Section: Discussionsupporting
confidence: 83%
“…The results of ALT and AST levels in plasma as well as H&E staining confirmed an injury of liver in adult mice as expected. Mice at younger ages were reported to be more resistant to AILI (Adamson et al, 1991). In the present study, the resistance to AILI in the mice at the infant age was further confirmed.…”
Section: Discussionsupporting
confidence: 83%
“…Previous reports [15,[22][23][24][25] have shown that the large dose of PC administration in the chronic manner resulted in the liver injury. Accordingly, PC had a negative influence upon liver metabolism by means of PC-protein adducts formation [26][27][28][29]. In our study we found clear-cut free radical-dependent mechanism of paracetamol toxic action influencing the rat liver after 8 and 12 weeks, when administered in a dose of 2.4 g/kg of body weigth/24 hrs, in a form of a potable solution.…”
Section: Discussionsupporting
confidence: 53%
“… 17 Furthermore, paracetamol metabolites detected in the urine from babies from breastfeeding mothers, differ significantly from those detected in the urine of healthy adults who have ingested paracetamol. Neonates have significantly higher levels of paracetamol in their urine compared with adults, and adults have greater levels of urinary paracetamol sulfate, 17 confirming that the pharmacokinetics and pharmacodynamics of paracetamol differ substantially in murine 28 and human neonates and infants compared with children and adults. 29 As it is technically very difficult to perform oral gavage in newborn mice, the importance of oral paracetamol ingestion in early life on subsequent AAD was indirectly determined in our study by administering paracetamol to mothers only during lactation and assessing AAD just prior to weaning at 3 weeks.…”
Section: Discussionmentioning
confidence: 91%